2014
DOI: 10.1093/gastro/gou022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of homocysteine on intestinal permeability in rats with experimental colitis, and its mechanism

Abstract: Objective: To investigate the effect of homocysteine (Hcy) on intestinal permeability in rats with TNBS/ethanol-induced colitis and elucidate its mechanism.Methods: Sprague-Dawley rats were divided into four groups: normal, normal + Hcy injection, TNBS model, and TNBS model + Hcy injection. Experimental colitis was induced by trinitrobenzene sulfonic acid (TNBS) in 50% ethanol; rats were injected subcutaneously with Hcy from the first day after the induction of experimental colitis on 30 consecutive days. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…We have now found that the inflamed ileum of CD patients did not show the expected cytokine profile with elevated expression of IFN-g in the affected ileal tissue. However, we have found increased IFN-g expression in the treated group, which might have resulted from sulphasalazine treatment that can up-regulate the expression of IFN-g (39). Furthermore, there was no difference in IL-6 or IL1b expression among the defined groups, although IL-6 was borderline significantly elevated in the untreated group (p=0.0625).…”
Section: Expression Of Cytokines and Socs Moleculesmentioning
confidence: 58%
“…We have now found that the inflamed ileum of CD patients did not show the expected cytokine profile with elevated expression of IFN-g in the affected ileal tissue. However, we have found increased IFN-g expression in the treated group, which might have resulted from sulphasalazine treatment that can up-regulate the expression of IFN-g (39). Furthermore, there was no difference in IL-6 or IL1b expression among the defined groups, although IL-6 was borderline significantly elevated in the untreated group (p=0.0625).…”
Section: Expression Of Cytokines and Socs Moleculesmentioning
confidence: 58%
“…Damage of intestinal barrier can aggravate mucosal inflammation, induce immune response, and is believed to be the key process responsible for infection‐ and immune factors‐initiated intestinal diseases including cancers (Bischoff et al, ). The proinflammatory cytokines, including TNF‐α and IL‐6, are known to disrupt tight junctions, decrease the transendothelial electrical resistance, and regulate the expression of intestinal mucosal barrier‐associated proteins, thereby increasing intestinal permeability (Ding et al, ). Significant reduction in serum TNF‐α level was observed on treatment with LAB ( p < .01), GE ( p < .001), and cobiotic ( p < .01).…”
Section: Resultsmentioning
confidence: 99%
“…One of the possible mechanisms by which Hhcy is implicated in colon inflammation disease is the fact that it leads to endothelial dysfunction [43] which facilitate immune cells infiltration in colonic tissue by an increase of leukocyte adhesiveness and leukocyte diapedesis [44].…”
Section: Discussionmentioning
confidence: 99%